INTEGRATED EFFORTS OF THE PEOPLE'S CARE MOVEMENT COMMUNITY IN TACKLING POVERTY - Surya, Rahadiyan; Anwar, Khairil; Zainiyah, Siti Ulfatuz (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This research discusses and efforts and solutions in overcoming or overcoming poverty. This study uses qualitative research methods. The data collection technique is carried out by literature study, namely exploring journals, good scientific journals and other information relevant to the research. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawn. By using several journals to be re-analyzed, the author finds efforts to overcome and also look for the most appropriate strategy in efforts to eradicate poverty. The researcher also briefly discussed the existing problems related to poverty by taking several concepts of the community program planning model of the people's care movement as an effort to alleviate poverty that can be taken to make a solution.